Assessing the regional impact of Japan's COVID-19 state of emergency declaration: a population-level observational study using social networking services. Issue 2 (15th February 2021) - Yoneoka, Daisuke; Shi, Shoi; Nomura, Shuhei; Tanoue, Yuta; Kawashima, Takayuki; Eguchi, Akifumi; Matsuura, Kentaro; Makiyama, Koji; Uryu, Shinya; Ejima, Keisuke; Sakamoto, Haruka; Taniguchi, Toshibumi; et al.
Abstract : Objective: On 7 April 2020, the Japanese government declared a state of emergency in response to the novel coronavirus outbreak. To estimate the impact of the declaration on regional cities with low numbers of COVID-19 cases, large-scale surveillance to capture the current epidemiological situation of COVID-19 was urgently conducted in this study. Design: Cohort study. Setting: Social networking service (SNS)-based online survey conducted in five prefectures of Japan: Tottori, Kagawa, Shimane, Tokushima and Okayama. Participants: 127 121 participants from the five prefectures surveyed between 24 March and 5 May 2020. Interventions: An SNS-based healthcare system named COOPERA (COvid-19: Operation for Personalized Empowerment to Render smart prevention And care seeking) was launched. It asks questions regarding postcode, personal information, preventive actions, and current and past symptoms related to COVID-19. Primary and secondary outcome measures: Empirical Bayes estimates of age-sex-standardised incidence rate (EBSIR) of symptoms and the spatial correlation between the number of those who reported having symptoms and the number of COVID-19 cases were examined to identify the geographical distribution of symptoms in the five prefectures. Results: 97.8% of participants had no subjective symptoms. We identified several geographical clusters of fever with significant spatial correlation (r=0.67) with the number of confirmed COVID-19 cases, especially in the urban centres of prefectural capital cities. Conclusions: Given that there are still several high-risk areas measured by EBSIR, careful discussion on which areas should be reopened at the end of the state of emergency is urgently required using real-time SNS system to monitor the nationwide epidemic.